Towards improving NFR elicitation in software development. - Too, Chian Wen; Hassan, Sa'adah; Din, Jamilah; Abd. Ghani, Abdul Azim (Institute of Information System & Research Center, 2013)
Non-functional requirement (NFR), such as performance, reliability, security and usability, have highly impact on the quality of software products. However, most of the current requirement elicitation processes are mainly focused on functional requirements (FR), while the NFR have received less attention. This paper provides literature on NFR elicitation in order to find out the reasons and problems of improper treatment in NFR. Essential issues on NFR elicitation include the approaches, elicitation techniques, methods and tools were addressed. Finally, some suggestions for improvement on NFR elicitation to be undertaken are also discussed.